Gingival crevicular glucose estimation and patient’s perception of pain during routine dental examination – a concept based on a novel patented periodontal device - AlQahtani, Nabeeh Abdullah; Khader, Mohasin Abdul; Javali, Mukhatar Ahmed (Vojnosanitetski pregled, 2023)
Background/Aim. Diabetes mellitus (DM) is a common metabolic disease that causes high mortality and morbidity worldwide. Therefore, in order to implement prevention strategies, physicians need to identify this condition as early as possible. The aim of the study was to test the concept of a novel periodontal device that can be attached to a glucose monitoring device as an innovative tool to screen for periodontitis and DM simultaneously during a routine dental examination. Hence, the correlation of blood glucose between the conventional finger-prick blood glucose (FPBG) and gingival crevicular blood glucose (GCBG) method, along with an estimation of the patient’s pain perception by visual analog scale (VAS) was examined. Methods. A cross-sectional comparative study was conducted among 250 participants whose GCBG and FPBG were estimated. The VAS score scale was recorded for each patient immediately after the procedure. Results. The mean GCBG value was 151.19 ± 42.64 mg/dL, while the mean FPBG was 150.48 ± 42.95 mg/dL, showing a high Pearson’s correlation (r = 0.9932; p < 0.00001). The Mann-Whitney U test for VAS score between both groups showed a statistically significant difference (p < 0.00001). Conclusion. The GCBG method was well tolerated by patients, and highly correlated with peripheral blood glucose levels. The proposed concept of the novel periodontal device appeared to be a feasible option for examining periodontium and screening DM simultaneously in dental clinics.
Keywords: blood glucose; dental instruments; diabetes mellitus; fingers; gingival crevicular fluids; pain measurement; periodontitis